ASSESSMENT OF BIOMASS, CARBON STOCK, AND CO₂ SEQUESTRATIONIN THE ARBORETUM OF INSTITUT TEKNOLOGI SUMATERA - Nurika Arum Sari; Fakhri Muhammad Fikri; Agung Yoga Pangestu; Diyanti IsnaniSiregar; Oktarina Maulidia (Jurnal Penelitian Kehutanan BONITA, 2026)
Global warming driven by rising greenhouse gas emissions has heightened the need to utilize green spaces as carbon sinks, one of which is the arboretum. This study aimed to determine the potential biomass, carbon stock, and CO₂ uptake of the vegetation in the Arboretum of Institut Teknologi Sumatera (Itera). A combination of destructive and non-destructive methods was applied across 12 plots representing three levels of vegetation density: high, medium, and low. The analysis covered biomass, carbon stock, and estimated CO₂ uptake. The results showed an average biomass of 50.51 tons/ha, a carbon stock of 23.74 tons/ha, and CO₂ uptake of 85.82 tons/ha. The highest values were found in the high-density vegetation area, which had a denser tree population. This study provides baseline carbon stock data for a developing campus arboretum in Sumatra, and concludes that, although the carbon stock of the Itera Arboretum remains lower than that of other arboreta, it nonetheless holds potential as a carbon sink that contributes to climate change mitigation. Practically, these results imply that arboretum management must prioritize intensive enrichment planting in low-density zones and establish permanent monitoring plots to optimize long-term carbon sequestration.